Problematika Mahasiswa PAI Universitas Negeri Padang dalam Penulisan Skripsi: Studi Kasus dan Upaya Solutif di Departemen - Arifin, Yulianda; Putra, Rido (TSAQOFAH, 2025)
This study is motivated by the limited research on the academic challenges faced by final-year students, particularly in the thesis writing process, which significantly contributes to delayed graduation and suboptimal academic achievement. The research aims to explore the obstacles encountered by students of the Islamic Religious Education (PAI) Study Program at Universitas Negeri Padang in thesis preparation, as well as to identify solution-oriented efforts by both students and the department. A qualitative approach was adopted using a case study design, involving ten participants selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s thematic analysis model. The findings reveal that the main barriers include difficulties in selecting a thesis topic, lack of motivation, challenges in academic supervision, low academic literacy, and social environmental influences. In response, students employed self-initiated strategies such as creating study schedules and actively sourcing literature, while the study program provided support through academic guidance and simplified administrative procedures. These findings reinforce the theory of self-regulated learning, which emphasizes the importance of autonomy and self-management in academic processes. The study concludes that a holistic approach, integrating students’ internal efforts with institutional academic policies is essential to accelerate degree completion. The implications include strengthening the academic literature on final-year student challenges and offering recommendations for developing adaptive mentoring systems in higher education.